Answer:(a)x^2+2y^2=2
(b)In the attached diagram
Step-by-step explanation:Step 1: Multiply both equations by t
xt=t(cost -sint)\\ty\sqrt{2} =t(cost +sint)
Step 1: Multiply both equations by t
xt=t(cost -sint)\\ty\sqrt{2} =t(cost +sint)
Step 2:We square both equations
(xt)^2=t^2(cost -sint)^2\\(ty)^2(\sqrt{2})^2 =t^2(cost +sint)^2
Step 3: Adding the two equations
(xt)^2+(ty)^2(\sqrt{2})^2=t^2(cost -sint)^2+t^2(cost +sint)^2\\t^2(x^2+2y^2)=t^2((cost -sint)^2+(cost +sint)^2)\\x^2+2y^2=(cost -sint)^2+(cost +sint)^2\\(cost -sint)^2+(cost +sint)^2=2\\x^2+2y^2=2 hopes this helps
The answer i came up with is 0.68 i don't know if thats what you need or not. hopefully i helped.
I=$52,000
R=6.75%
T=5.5 years
P=$19,305
Answer:
66.666666666667% error
Step-by-step explanation:
Percent Error = Vobserved - Vtrue / Vtrue
= 9 - 27 / 27
= -18/27
= -66.666666666667%
= 66.666666666667% error
I hope this helps!